2019
DOI: 10.3892/or.2019.7026
|View full text |Cite
|
Sign up to set email alerts
|

TNF‑α inhibits xenograft tumor formation by A549 lung cancer cells in nude mice via the HIF‑1α/VASP signaling pathway

Abstract: Lung cancer is the leading cause of cancer-associated mortality worldwide. Tumor necrosis factor α (TNF-α) is an important cytokine in the tumor microenvironment that serves a function in the balance of cell survival and cell death pathways. Our previous studies indicated that hypoxia-inducible factor 1α (HIF-1α) acts downstream of TNF-α in MCF-7 luminal breast cancer cells. However, whether vasodilator-stimulated phosphoprotein (VASP) is implicated in the direct regulation of HIF-1α in response to TNF-α in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…TNF-α is a pleiotropic proinflammatory cytokine that regulates a variety of physiological and pathological signaling pathways including as inflammation, differentiation, proliferation, and apoptosis induction. TNF-α promotes cancer cell proliferation, migration, and adhesion in the tumor microenvironment, accelerating multistep cancer development (Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a pleiotropic proinflammatory cytokine that regulates a variety of physiological and pathological signaling pathways including as inflammation, differentiation, proliferation, and apoptosis induction. TNF-α promotes cancer cell proliferation, migration, and adhesion in the tumor microenvironment, accelerating multistep cancer development (Liu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that under normoxic conditions stimulation of human intestinal epithelial Caco-2 cells with pro-inflammatory cytokines including TNF-α downregulated PHD1 mRNA levels which were correlated with decreased CCAAT-enhancer binding protein (C/EBPα) mRNA and protein expression, suggesting that the effect of TNF-α on the C/EBPα/PHD1 mechanism could lead to increased HIF-1α stabilization in the mucosal tissue of UC patients [ 12 ]. TNF-α treatment also significantly upregulates HIF-1α protein and mRNA levels in human squamous lung A549 and H226 cells, which inhibits A549 cell proliferation and adhesion as well as TNF-α-activated transcriptional activity of HIF-1α, resulting in suppression of vasodilator-stimulated phosphoprotein (VASP) and consequent inhibition of transplanted tumors growth in nude mice [ 64 ]. Taken together, TNF-α can be considered a modulator of the sensitivity of the HIF pathway to hypoxia in inflamed cells and its regulatory and constituent components, thus modulating protective HIF responses in different cell types and tissues.…”
Section: Regulation Of Hif By Cytokinesmentioning
confidence: 99%
“…Zeya et al [ 11 ] found that LOX-1 interacts with its ligands to induce the expression of inflammatory cytokines such as IL-1 β and TNF- α . In addition, studies have found that IL-1 β promotes the invasion and metastasis of lung cancer A549 cell line, thereby promoting the progression and metastasis of cancer, and TNF- α could promote the metastasis of lung cancer by inducing EMT [ 28 , 29 ]. Studies have shown that LOX-1 participates in the cross presentation of antigens, exerts the targeted effect of immune activation and antigen transmission, inhibits the attack of the immune system, and promotes tumor progression [ 11 ].…”
Section: Discussionmentioning
confidence: 99%